2012
DOI: 10.1017/s1368980011003429
|View full text |Cite
|
Sign up to set email alerts
|

Is the Mediterranean diet adequate to satisfy zinc requirements during adolescence?

Abstract: Objective: To evaluate Zn utilization and status among a sample of Spanish boys consuming a diet based on Mediterranean patterns. Design: Dietary Zn balance was assessed by means of Zn intake in food and Zn output in faeces and urine as measured by flame atomic absorption spectrophotometry. In addition, biomarkers of Zn status were analysed. Setting: Province of Granada, Spain. Subjects: Twenty healthy male adolescents aged 11-14 years, selected based on medical questionnaire, physical examination and nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…A study conducted in Spain showed that 20 healthy male adolescents aged 11–14 with a diet based on the MDP allowed to maintain adequate zinc serum levels despite the content of dietary phytate, which is present in vegetables, cereals and legumes [56]. In the same age group, there is evidence that when a MDP was consumed, a drastic increase in iron absorption was observed among the subjects when compared to their habitual diet [57].…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in Spain showed that 20 healthy male adolescents aged 11–14 with a diet based on the MDP allowed to maintain adequate zinc serum levels despite the content of dietary phytate, which is present in vegetables, cereals and legumes [56]. In the same age group, there is evidence that when a MDP was consumed, a drastic increase in iron absorption was observed among the subjects when compared to their habitual diet [57].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that various foods and nutrients may play a role in RCC risk (2,3). Dietary intake of fiber and fiber-rich foods (4), vitamins (5,6), fat (7), proteins (8), fruits (9), vegetables (10,11), and red meat (6,11) have been associated with RCC etiology in some studies but not in others (12)(13)(14). Therefore, associations between dietary intake and RCC etiology remain inconclusive.…”
mentioning
confidence: 99%
“…It is of interest to note that low serum micronutrient levels were observed in patients with Major Depressive Disorder and although the etiopathogenic role of trace elements in different disease states should be furtherly studied, it is possible that MD could benefit them. Moreover, it seems that there is an association between the serum trace element levels and developmental dysplasia of the hip [ 21 , 22 , 23 ].…”
Section: Role Of Mediterranean Diet Components On Inflammatory Resmentioning
confidence: 99%